Plasma and Urinary Levels of Nerve Growth Factor Are Elevated in Primary Hypertension - Fumihiro Tomoda; Atsumi Nitta; Hiroko Sugimori; Tsutomu Koike; Koichiro Kinugawa (International Journal of Hypertension)
Nerve growth factor (NGF) is the main neurotrophic factor that can control sympathetic nerve innervation and sympathetic neural activity in cardiovascular organs. Although NGF overproduction and its influences on the sympathetic nervous system have been shown in hypertensive animals, NGF status and its association with sympathetic nerve activity have not yet been explored in human hypertension. In the present study, therefore, plasma and urinary levels of NGF and those of catecholamines (i.e., indices for NGF status and sympathoadrenal activity, respectively) were compared between 83 untreated primary hypertensives without apparent cardiovascular damages and 81 healthy normotensive subjects. Plasma and urinary levels of NGF were significantly greater in the hypertensive group (311 ± 158 pg/mL and 72.7 ± 54.0 ng/g of Cr) than in the normotensive group (168 ± 188 pg/mL and 54.5 ± 38.8 ng/g of Cr) (p<0.05 for each measurement), even if the baseline differences of age and gender between the groups were adjusted. Similarly, plasma and urinary levels of catecholamines were significantly higher in the hypertensive group than in the normotensive group except for plasma noradrenaline. In addition, despite no significant correlations between plasma levels of NGF and catecholamines in both groups, urinary NGF significantly correlated positively with both urinary noradrenaline and urinary adrenaline in the hypertensive group (r = 0.259, p=0.018 and r = 0.232, p=0.035), but not in the normotensive group (r = 0.115, p=0.307 and r = −0.018, p=0.871). On the contrary, plasma and urinary levels of NGF as well as those of catecholamines did not associate with any systemic hemodynamic indices such as blood pressure and pulse rate in either group. Thus, primary hypertension was characterized by the enhancements of both NGF status and sympathoadrenal activity and the positive relationship between them. Our data indicate that enhanced NGF status and subsequent NGF-induced sympathoadrenal overactivity could occur in primary hypertension.